Methods for soil infestation with Striga hermonthica seeds - Berner, D.; Ikie, F.O.; Aigbokhan, E.I. (Wiley, 1996)
Field screening of maize (Zea mays L.) and sorghum [Sorghum bicolor (L.) Moench] can be an efficient means of selecting for resistance to the parasitic plant Striga hermonthica (Del.) Benth. Spatial variability in natural S. hermonthica seed infestations necessitates supplemental infestation for effective field screening. For uniformly heavy levels of infestation, sieved sand has been used as a carrier material for the extremely small S. hermonthica seeds, and a 7- to 14-d waiting period between infestation and planting is often provided to environmentally condition the S. hermonthica seeds for germination and uniform infection. These steps are labor-intensive, requiring sieving of large amounts of sand and separate infestation and planting times. The objective of this study was to develop alternative soil infestation methods for S. hermonthica seeds that require less labor and produce levels of infection comparable to standard procedures. Nine different methods of soil infestation with S. hermonthica seeds were tested in a screenhouse and in two field locations on maize and sorghum cultivars. To assess effectiveness of the methods, S. hermonthica emergence and host yield were measured. Infestation using sand as a carrier material followed by a 14-d in situ conditioning period resulted in the greatest amount of infection in the screenhouse. In the field, methods that employed no conditioning period, and thus allowed infestation and planting on the same day, produced levels of infection comparable to methods with 7- and 14-d preplant conditioning periods. The most easily accomplished of these methods used water as the carrier material, producing levels of infection equivalent to methods using sand.